2003
DOI: 10.1073/pnas.1631069100
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal circadian secretion of melatonin from the pineal gland in a living CBA mouse

Abstract: Circadian melatonin secretion is the best-known output signal from the circadian pacemaker in the suprachiasmatic nucleus that indicates internal conditions of the body. We have established a system that enables long-term monitoring of melatonin secretion by implanting a transverse microdialysis probe in or near the pineal gland in a freely moving mouse. This in vivo method enabled continuous measurement of melatonin secretion over a period of >20 days in individual CBA mice, with simultaneous recording of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…The observed 12h ultradian rhythm in the 'blind' mole rats is characterized by acrophase occurring around the onset and the offset of the scotophase. An ultradian rhythm of MEL secretion with two peaks, one in the evening and the other in the morning, has also been reported previously (Arendt, 1985;Wehr et al, 1995;Nakahara et al, 2003). The bimodal rhythm of MEL has been suggested to reflect the separate regulation of two different oscillators.…”
Section: Discussionsupporting
confidence: 75%
“…The observed 12h ultradian rhythm in the 'blind' mole rats is characterized by acrophase occurring around the onset and the offset of the scotophase. An ultradian rhythm of MEL secretion with two peaks, one in the evening and the other in the morning, has also been reported previously (Arendt, 1985;Wehr et al, 1995;Nakahara et al, 2003). The bimodal rhythm of MEL has been suggested to reflect the separate regulation of two different oscillators.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, hemolymph 5-HT sulfate is most probably originating from the nervous system. In mammals, the 5-HT metabolite/hormone, melatonin, under control of the circadian pacemaker, is released at much higher concentrations during night than day (Nakahara et al 2003). Melatonin is the signal for quiescence in both diurnal and nocturnal animals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two relatively different daily rhythms in 6-SMT were observed, but both rhythms appeared to be ultradian. Ultradian patterns of melatonin secretion have previously been observed in humans and in mice, and it has been suggested that two separate oscillators are foundational to these patterns (Wehr et al, 1995;Nakahara et al, 2003). Evidence also suggests that daytime and night-time melatonin are regulated by different processes.…”
Section: Urinary 6-smt Concentrationmentioning
confidence: 95%
“…At night, neurological signals from the superior cervical ganglia stimulate the rise in pineal melatonin production via sympathetic nerves (Moore, 1996;Reiter et al, 2011). In CBA mice, application of tetrodotoxin, a Na + channel blocker, effectively suppresses neurological stimulation of pineal melatonin production by night, but not by day (Nakahara et al, 2003). It has therefore been suggested that daytime melatonin regulation primarily results from endogenous activation inside the pinealocyte (Li et al, 2000).…”
Section: Urinary 6-smt Concentrationmentioning
confidence: 99%